A randomised, open‐label, crossover study of the dopamine agonist, pramipexole, in patients with sleep bruxism. (17th July 2016) - Cahlin, Birgitta Johansson; Hedner, Jan; Dahlström, Lars
Summary: Sleep bruxism bears several similarities to restless legs syndrome, and a link to changes in central dopamine activity has been considered in both conditions. The dopamine agonist pramipexole is currently indicated for the symptomatic treatment of restless legs. The effect of pramipexole on sleep bruxism was investigated in subjects with 'probable bruxism' recruited at the Orofacial Pain Clinic. Thirteen patients underwent polysomnographic recordings, including bilateral masseter electromyographic activity. Following habituation to the recording equipment, a baseline registration was used to confirm bruxism [total episodes per hour, mean 11.3 (6.3)]. Following randomisation, subjects received no treatment or pramipexole titrated from 0.09 to 0.54 mg, o.d., for 3 weeks according to a crossover procedure. A polysomnographic‐electromyographic registration was performed at the end of each period. Pramipexole was associated with more frequent awakenings and a reduction in rapid eye movement sleep (both P  ≤ 0.02). Sleep apnea decreased marginally after pramipexole (apnea–hypopnea index 17.1 compared with control 21.5, P  ≤ 0.05). The number of bruxism episodes, phasic, tonic and mixed per hour, remained unchanged after pramipexole [total episodes per hour 12.7 (8.5) and 9.8 (5.2) during pramipexole and control conditions, respectively]. It is concluded, from this pilot study, that sleep bruxism is not affected by the dopaminergic agent, pramipexole.